Difficult Biliary Cannulation for Intradiverticular Papilla: Forceps Technique Revisited - Goenka, Mahesh Kumar; Rodge, Gajanan Ashokrao; Shah, Bhavik Bharat; Afzalpurkar, Shivaraj (The Surgery Journal, 2021)
Periampullary diverticula (PAD) have been encountered in 5.9 to 18.5% of patients during all the endoscopic retrograde cholangiopancreatography (ERCP). Cannulation in the presence of PAD can sometimes be difficult, time consuming, and often requires a higher level of endoscopic skills.Several techniques have been reported to facilitate and increase the chances of successful bile duct cannulation in the presence of PAD. The two-devices in one-channel method has been sparingly used. It involves the simultaneous use of a biopsy forceps and another instrument, either a cannula or sphincterotome through the same working channel. We successfully performed ERCP in three cases, where bile duct cannulation was performed in the setting of intradiverticular papilla using two-devices in one-channel method.We feel that the two-devices in one-channel method can be very useful and positioned higher up in the algorithm for successful cannulation in patients with PAD.
Keywords: periampullary diverticula; ERCP; two-devices in one-channel method; difficult biliary cannulation